2016
DOI: 10.1128/aac.01503-16
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Outcomes, and Mechanisms of Tigecycline-Nonsusceptible Klebsiella pneumoniae Bacteremia

Abstract: A rise in tigecycline resistance in Klebsiella pneumoniae has been reported recently worldwide. We sought to identify risk factors, outcomes, and mechanisms for adult patients with tigecycline-nonsusceptible K. pneumoniae bacteremia in Taiwan. We conducted a matched case-control study (ratio of 1:1) in a medical center in Taiwan from January 2011 through June 2015. The cases were patients with tigecycline-nonsusceptible K. pneumoniae bacteremia, and the controls were patients with tigecyclinesusceptible K. pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…A literature review showed that reported mechanisms in tigecycline resistance of K . pneumoniae include overexpression of ramA and acrAB [9, 31, 32], deletions, insertions and point mutations in ramR [33, 34], overexpression of rarA and oqxB [9, 32, 35], a point mutation in the repressor oqxR and overexpression of the OqxAB efflux pump [13], IS 5 element integration in a putative efflux pump, KpgABC [23], overexpression of marA and acrAB , and structural alteration of the ribosomal protein S10 [34]. The detailed role of each mechanism in conferring tigecycline resistance requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review showed that reported mechanisms in tigecycline resistance of K . pneumoniae include overexpression of ramA and acrAB [9, 31, 32], deletions, insertions and point mutations in ramR [33, 34], overexpression of rarA and oqxB [9, 32, 35], a point mutation in the repressor oqxR and overexpression of the OqxAB efflux pump [13], IS 5 element integration in a putative efflux pump, KpgABC [23], overexpression of marA and acrAB , and structural alteration of the ribosomal protein S10 [34]. The detailed role of each mechanism in conferring tigecycline resistance requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The first report of oqxAB was from a plasmid in E. coli in 2004 35 . An ortholog of oqxAB was not found in the E. coli genome, but was found in the K. pneumoniae genome 36 . Several transcriptional regulator genes were located in the flanking regions of oqxAB in the K. pneumoniae genome, and it was also reported that both rarA, located upstream of oqxAB, and oqxR, downstream of oqxAB, were regulator genes of oqxAB 5,37 .…”
Section: Gene Cloning Of Deduced Rnd-type Multidrug Efflux Pumps Thementioning
confidence: 99%
“…Thus, we also detected acrE and acrF, but no increase in expression was observed. Juan et al (2016) evaluated 43 strains each of tigecycline-non-susceptible KP and tigecycline-susceptible KP, and found that the overexpression of OqxAB efflux pumps was a major cause of tigecycline-non-susceptible KP resistance to tigecycline. However, the evolved strains in this study did not show an increase in their expression.…”
Section: Discussionmentioning
confidence: 99%